Comparison of General and Spinal Anesthesia in Cervical Cancer Patients Undergoing Intracavitary Brachytherapy: An Observational Comparative Study - Nopian Hidayat; Pratama Ananda; Dino Irawan; Novita Anggraeni; Sony; Patricia Feliani Sitohang (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Intracavitary brachytherapy is a fundamental modality in the management of cervical cancer. The procedure often induces significant discomfort due to applicator insertion and patient immobilization, making appropriate anesthetic management essential. General anesthesia (GA) and spinal anesthesia (SA) are commonly applied; however, their relative impact on perioperative outcomes remains a subject of debate. Objective: This study aimed to evaluate and compare the effects of GA and SA in patients with cervical cancer undergoing intracavitary brachytherapy, with particular emphasis on hemodynamic stability, postoperative pain intensity, recovery duration, and anesthesia-related complications. Methods: This observational analytic comparative study was conducted at Arifin Achmad General Hospital, Pekanbaru, Indonesia, following ethical approval. Fifty ASA II cervical cancer patients scheduled for intracavitary brachytherapy were enrolled and allocated into two groups: GA (n=25) and SA (n=25). Intraoperative hemodynamic variables were continuously monitored. Postoperative pain was assessed using the Numeric Rating Scale (NRS) at 0, 2, 4, 6, 12, and 24 hours. Recovery time, rescue analgesia requirement, and perioperative complications were recorded. Data were analyzed using Mann–Whitney U and Chi-square tests, with p<0.05 considered statistically significant. Results: Baseline characteristics were comparable between groups. No significant differences were observed in intraoperative hemodynamic parameters (p=0.930). The SA group demonstrated significantly lower pain scores at 0 hours (mean rank 15.12 vs 35.88; p<0.001) and 6 hours postoperatively (mean rank 19.68 vs 31.32; p=0.002), while no difference was found at 24 hours (p = 0.270). Rescue analgesia was required only in the GA group (16% vs 0%; p = 0.038). Recovery time was significantly shorter in the GA group (mean rank 20.24 vs 30.76; p=0.009). No anesthesia-related complications were observed. Conclusion: Both GA and SA are safe and effective for intracavitary brachytherapy. SA provides superior early postoperative analgesia with reduced need for rescue analgesia, whereas GA offers faster recovery. Anesthetic selection should be tailored to clinical priorities.